2021
DOI: 10.3390/vetsci8060096
|View full text |Cite
|
Sign up to set email alerts
|

Different Non-Structural Carbohydrates/Crude Proteins (NCS/CP) Ratios in Diet Shape the Gastrointestinal Microbiota of Water Buffalo

Abstract: The microbiota of the gastrointestinal tract (GIT) are crucial for host health and production efficiency in ruminants. Its microbial composition can be influenced by several endogenous and exogenous factors. In the beef and dairy industry, the possibility to manipulate gut microbiota by diet and management can have important health and economic implications. The aims of this study were to characterize the different GIT site microbiota in water buffalo and evaluate the influence of diet on GIT microbiota in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Among them, Anabaena phylum, thick-walled phylum and Aspergillus phylum were the most abundant phyla in all gut sites; this result was particularly evident in the large intestine. This suggests that diet can strongly influence the microbiota at different gut sites [38]. In addition, we observed a high relative abundance of Blautia, a member of the thick-walled bacterium family Trichodermaceae, which converts undigested carbohydrates and proteins into acetic acid, which then produces energy for the organism, with anti-inflammatory effects and the ability to improve the host intestinal environment and lipid metabolism [39].…”
Section: Discussionmentioning
confidence: 83%
“…Among them, Anabaena phylum, thick-walled phylum and Aspergillus phylum were the most abundant phyla in all gut sites; this result was particularly evident in the large intestine. This suggests that diet can strongly influence the microbiota at different gut sites [38]. In addition, we observed a high relative abundance of Blautia, a member of the thick-walled bacterium family Trichodermaceae, which converts undigested carbohydrates and proteins into acetic acid, which then produces energy for the organism, with anti-inflammatory effects and the ability to improve the host intestinal environment and lipid metabolism [39].…”
Section: Discussionmentioning
confidence: 83%
“…Lactobacillus , and Akkermansia ( Amabebe et al., 2020 ). However, gastrointestinal microbes of different intestinal segments in cattle, sheep, and panda have existed the differences for digesting crude fiber diet, such as Bacteroidetes , Firmicutes and Proteobacteria , Streptococcus , Clostridium , Escherichia ( Paradiso et al., 2021 ; Deng et al., 2023 ; Long et al., 2024 ). In this study, three key microbial species in cecum ( Mycoplasma_sp._CAG:472 , Clostridium_sp._CAG:793 , and Akkermansia glycaniphila ) were inconsistent with the above research results.…”
Section: Discussionmentioning
confidence: 99%
“…With the in-depth study of intestinal microbiota, it is found that the host's health is greatly affected by them [ 2 ], can provide nutrition for the body, regulates metabolism and intestinal epithelial development, and induces innate immunity [ 3 ]. In addition, studies have also proved that intestinal microorganisms are the guarantee for ruminants to digest, feed, establish the immune system, and give play to production performance [ 4 , 5 ]. Previously, studies have reported the rumen bacterial diversity and the composition and diversity of bacteria in the small intestine and cecum of adult yaks [ 6 ].…”
Section: Introductionmentioning
confidence: 99%